Design of Automatic Fruit Juice Pasteurization Machine Based on Ohmic Heating Technology - Adilaksono, Indrawan Cahyo; Susilo, Bambang; Sugiarto, Yusron (Jurnal Teknologi Pertanian, 2014)
Fruit production in Indonesia has greatly increased year by year that is resulting in price fluctuation due to abundant products. The fruits possible to be rotten which decrease the sale value when the harvest time is unstable. One of the efforts for increasing the sale value of fruit is by making juice. The most important process of making juice is pasteurization. Ohmic heating pasteurization is one of pasteurization methods that can be utilized to pasteurize the juice. Thus, the juice pasteurization machine was created in particular design to pasteurize juice in small-scale. This study aims to determine the design of machine and the performance machine test, and to determine the efficiency of energy use of machine performance. Performance testing of energy efficiency of fruit juice pasteurization was carried out in an ohmic tube with a diameter of 3.55 cm and electrode spacing of 18 cm. The experiment used mango as a sample with the addition of water (2:1), the sample was pasteurized with 3 variations of electric potential included 220V, 385V, and 425V up to 800C. The highest energy efficiency up to 94%. It was obtained in voltage of 385 V with pasteurization time 130 s and the lowest energy efficiency up to 88%. It was obtained in voltage of 220 V with pasteurization time 369 s. The result showed that the ohmic-based fruit juice pasteurization machine was able to pasteurize in short time and had high efficiency.Keywords: Ohmic Heating, Efficiency, Pasteurization